Erwinia psidii - Eucalyptus spp.: colonization, genetic variability, aggressiveness and immunological test for pathogen detection - Montoya Estrada, Claudia Nohemy (2018)
Dieback, caused by Erwinia psidii is currently one of the most severe emerging diseases in eucalypt plantations. Despite its economic importance, due to the risks posed to eucalypt production, little is known about this pathosystem. In this work, we studied the plant colonization by a gfp-transformed E. psidii isolate using histological sections, estimated the genetic variability of pathogen populations using molecular rep–PCR markers (ERIC, REP and BOX) and developed an immunoassay for the rapid detection of E. psidii in symptomatic and asymptomatic plants. In this study, we were able to transform E. psidii with pGreen-TIR and to demonstrate that the plasmid is stable in the absence of antibiotic selection both in vitro and in vivo. Using fluorescence microscopy, it was possible to demonstrate that tissue colonization by E. psidii is not restricted to the inoculation point (leaf axil) and that it colonizes the xylem vessels, sclerenchyma and parenchyma of the leaves and stem of eucalypt. At 35 days after inoculation (dai), the bacterium was found at 5 cm above the inoculation point, indicating that it was able to colonize the plant acropetally, following the water flow. Confocal microscopy analysis of plant samples inoculated via radicular system revealed that E. psidii penetrates and colonizes primary and secondary roots and reaches the xylem vessels. However, at the times after inoculation evaluated in this study, the bacterium was restricted to the roots and did not reach the stem of the plant. Further studies with longer times after inoculation must be performed to confirm these results. It is believed that E. psidii is disseminated from infected asymptomatic cuttings. Molecular analyzes (rep-PCR) of 101 E. psidii isolates obtained from eucalypt (Eucalyptus spp.) and five guava (Psidium guajava) demonstrated that the populations in Brazil have low genetic variability. Nonetheless, grouping of isolates by host plant was observed, although two guava isolates (LPF681 and LPF682) grouped with eucalypt isolates (LPF609). The Wilcoxon and ANOVA tests on disease severity and AUDPC data indicated an isolate × clone interaction. AUDPC and disease severity varied significantly among isolates and between the two clones tested. The variability in aggressiveness among isolates of E. psidii demonstrated the importance of using the most aggressive isolates in the selection of resistant eucalypt genotypes for commercial scale planting. An antiserum against E. psidii isolate LPF534 (Anti-Ep) obtained in this study reacted positively against all strains of E. psidii tested, including some isolated from guava. The agglutination test designed using this antiserum can be considered important for the diagnosis of E. psidii, as it represents a rapid and low-cost alternative compared to PCR-based methods for detecting the pathogen in asymptomatic plants.